2006
DOI: 10.4049/jimmunol.177.11.7505
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: TLR3 Stimulation Suppresses Experimental Autoimmune Encephalomyelitis by Inducing Endogenous IFN-β

Abstract: Experimental autoimmune encephalomyelitis is a well-characterized model of cell-mediated autoimmunity. TLRs expressed on APCs recognize microbial components and induce innate immune responses, leading to the elimination of invading infectious agents. Certain TLR agonists have been reported to have adjuvant properties in CNS autoimmune inflammatory demyelination. We report in this study that TLR3 stimulation by polyinosinic-polycytidylic acid, a double-stranded RNA analog, suppresses relapsing demyelination in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 22 publications
(30 reference statements)
6
99
0
1
Order By: Relevance
“…Touil et al 44 have shown that TLR3 stimulation with the TLR3 agonist polyinosinic:polycytidylic acid (double-stranded RNA analog) suppressed demyelization in SJL/J mice with EAE by inducing IFN-b. The IFN-b upregulation that we obtained is most likely dependent on signaling from other sensors than TLR3 since we obtained a decrease in TLR3 mRNA expression after treatment with HSV-1 expressing IL-5 or IL-10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Touil et al 44 have shown that TLR3 stimulation with the TLR3 agonist polyinosinic:polycytidylic acid (double-stranded RNA analog) suppressed demyelization in SJL/J mice with EAE by inducing IFN-b. The IFN-b upregulation that we obtained is most likely dependent on signaling from other sensors than TLR3 since we obtained a decrease in TLR3 mRNA expression after treatment with HSV-1 expressing IL-5 or IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 On the other hand, TLR stimulation can also suppress autoimmune pathogenesis, showing a more complex role for TLR in autoimmune diseases. 43,44 Vectors based on herpes simplex virus type 1 (HSV-1) have several features making them a good candidate for gene therapy of CNS disease. HSV-1 is naturally neurotropic, thus after primary infection of epithelial cells, the virus is transported along nerves to the sensory ganglia, where it can establish a latent infection.…”
Section: Multiple Sclerosis (Ms) Is a Demyelinating Autoimmune Diseasmentioning
confidence: 99%
“…It has recently been reported that PolyI:C suppresses relapses of EAE in SJL/J mice (Touil et al 2006). This TLR3 agonist induced IFN-β, which regulates EAE and has therapeutic efficacy in some MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example TLR4 knockout mice have greater disease severity which is associated with increased Th17 function [54], while determining the contribution of TLR9 has produced conflicting results [49,54]. In contrast TLR3 stimulation is protective in EAE due to the induction of IFNβ [55] which has led to the suggestion that TLRs inducing interferon is protective, whereas TLR stimulation that leads to proinflammatory cytokine expression adds to disease severity [56]. In addition to this, the immune cells which express TLRs have an important bearing on the disease.…”
mentioning
confidence: 99%